Petiolar Anatomy as an Aid in Taxonomy of the Genus Ixora L. (Rubiaceae) - Patil, C R; Patil, D A (Plantae Scientia, 2020)
The present authors investigated petiolar anatomy of 12 species of the genus Ixora L. (Rubiaceae). The petioles (in T.S.) are horse shoe-shaped, planoconvex or circular in outline. They are usually winged and channeled adaxially. The extent of development of various tissues and their distribution, besides the cell inclusions, are observed. The vasculature is resolved into a conspicuous central arc, besides few other vascular bundles. The central arc is horse shoe-shaped, heart-shaped, circular, lunar or crescent shaped. The vascular arcs or bundles are capped abaxially by few sclerenchymatous layers, except few. The shapes of petiole, petiolar wings, features of epidermis, patterns of vascular supply and association of sclerenchyma with it, cell contents, etc. are thought systematically important. All these features are employed to prepare a key helping identification of the taxa investigated.